Pointwise Estimates of Solutions for the Viscous Cahn-Hilliard Equation with Inertial Term. (23rd June 2020) - Li, Nianying; Yin, Li; You, Honglian
Abstract : In this paper, we study the pointwise estimates of solutions to the viscous Cahn-Hilliard equation with the inertial term in multidimensions. We use Green's function method. Our approach is based on a detailed analysis on the Green's function of the linear system. And we get the solution's L p convergence rate.